Assessment of the teaching performance favors to creativity in a sample of Colombian public and private educational institutions - Klimenko, Olena; Hernández-Flórez, Nubia Ester; Tamayo-Lopera, Diego Alfredo; Cudris-Torres, Lorena; Niño-Vega, Jorge Armando; Vizcaino-Escobar, Annia Esther (Universidad Pedagógica y Tecnológica de Colombia, 2023)
The present study was oriented to assess the teaching performance that favors creativity from the teaching practices, contrasting it with the type of educational institution, pedagogical model, creativity and academic score of the students in a sample of the educational institutions of the Aburrá Valley. A quantitative, non-experimental, ex post facto study was carried out with 210 teachers and 950 students from 10 educational institutions. The Likert scale of teaching performance designed adhoc, and the PIC-J test were used. The results indicate that the use of cognitive mediation strategies for divergent thinking and the use of flexible and open evaluation strategies are related to higher creativity scores in students. The implications for educational processes and the need to implement innovative pedagogical and didactic strategies to reorient the emphasis of rote methodologies towards creative learning are discussed.